2010
DOI: 10.4305/metu.jfa.2010.2.19
|View full text |Cite
|
Sign up to set email alerts
|

Invigorating Industrial Design Materials and Manufacturing Education

Abstract: well established, but selection for product expression/personality is underdeveloped. Recently a body of new research has emerged taking a humanistic perspective to the selection of materials for industrially manufactured products. The common point is to articulate ways in which designers can use materials to affect people's experiences of products on aesthetic, meaning and emotional levels, within a wider context of product differentiation, branding, and other commercial imperatives. Accompanying this new bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
11

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 25 publications
(21 reference statements)
0
26
0
11
Order By: Relevance
“…producing complex shapes) that added value that more than compensated for the higher part cost. This might reflect that, although cost is a crucial factor for designers in materials and process selection, it is not necessarily the dominant driver in itself (Pedgley 2009). Designers may favour more expensive AM processes over conventional alternatives because they may be able deliver long term economic benefits (e.g.…”
Section: Advantages and Limitations Of Am For Series Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…producing complex shapes) that added value that more than compensated for the higher part cost. This might reflect that, although cost is a crucial factor for designers in materials and process selection, it is not necessarily the dominant driver in itself (Pedgley 2009). Designers may favour more expensive AM processes over conventional alternatives because they may be able deliver long term economic benefits (e.g.…”
Section: Advantages and Limitations Of Am For Series Productionmentioning
confidence: 99%
“…It has previously been identified that the choice of manufacturing processes by designers are often constrained (or directed) by convenience (e.g. Pedgley 2009) and not necessarily for technical or knowledge reasons. This might indicate that although AM could theoretically be recognised as the most suitable production solution, it requires a change in existing designers' practices.…”
Section: Knowledge Of Design Principles and Design Rules For Ammentioning
confidence: 99%
“…Therefore, this study refers instead to industrial designers' participation in new PSS development. Although the concept of industrial design has been defined in various ways (Verganti, 2008), it is agreed that it is responsible for a product's appearance and user-friendliness, among other things (Gemser & Leenders, 2001;Pedgley, 2009). Gorb and Dumas (1987) determined a process by which non-designers are engaged in design.…”
Section: Methodsmentioning
confidence: 99%
“…Adding this to the model emphasises that in practice product designers often start their materials selection process already with a set of commonly used materials in their mind. This point is emphasized by the practical constraints and directions imposed on materials selection identified by Pedgley (2009).…”
Section: Validation Of the Modelmentioning
confidence: 99%